THE ISSUE OF CYBER SECUTIRY IN RAIL TRAN SPORT (Perner's Contacts, 2018)
This article deals with the issue of cyber security in rail transport, especially the rail infrastructure manager point of view. It is explained, why the railway infrastructure manager is the critical information infrastructure administrator, which security measures should he apply and which imperfections there should be found in the implementation of this issue by auditors.
Keywords: security measures, cyber security, rail infrastructure manager